Intertwining Innovative Teaching–Learning Practices in Classrooms - Singh, Sunita (THE PRIMARY TEACHER, 2018)
Education is the way to progress and lays the very foundation of society. Given the rapid advancements in knowledge, science and technology, the quality of education being imparted is of paramount importance. But with an array of information available online, imparting knowledge and information has become an even more daunting task for educationists, especially, those catering to the primary stage. The young mind is inquisitive by nature, i.e., full of questions and information. As teachers are the most effective interface between students and knowledge, they need to possess a desired set of skills and be updated at all times in order to cater to the myriad needs of the young learners. They need to use different teaching– learning methodologies and strategies in classrooms, apart from conventional methods like lecture and chalk-and-talk, so as to enable the learners to have a clearer understanding of concepts. This paper describes different teaching–learning methods like blended learning, peer learning and peer tutoring that would make the teaching–learning process more insightful, impactful, interesting and interactive